2017
DOI: 10.1098/rsta.2016.0108
|View full text |Cite
|
Sign up to set email alerts
|

Towards reduced order modelling for predicting the dynamics of coherent vorticity structures within wind turbine wakes

Abstract: The dynamics of the velocity field resulting from the interaction between the atmospheric boundary layer and a wind turbine array can affect significantly the performance of a wind power plant and the durability of wind turbines. In this work, dynamics in wind turbine wakes and instabilities of helicoidal tip vortices are detected and characterized through modal decomposition techniques. The dataset under examination consists of snapshots of the velocity field obtained from large-eddy simulations (LES) of an i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 30 publications
(46 reference statements)
0
34
0
Order By: Relevance
“…It has been shown that a few spatial modes can already capture important features of the wake flow [35][36][37][38][39]41,43,47]. In the case of a large eddy simulation of an infinite row of turbines, Andersen et al [35] found that a few modes stemming from the proper orthogonal decomposition (POD) already yield a good description of the velocity field on large spatial scales.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been shown that a few spatial modes can already capture important features of the wake flow [35][36][37][38][39]41,43,47]. In the case of a large eddy simulation of an infinite row of turbines, Andersen et al [35] found that a few modes stemming from the proper orthogonal decomposition (POD) already yield a good description of the velocity field on large spatial scales.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the description and inclusion of a turbulent atmospheric inflow is a very challenging task. An alternative approach, investigated by Iungo et al [41], Debnath et al [43], is to linearize the temporal evolution leading to the dynamic mode decomposition [50][51][52][53]. In this framework, the relevant weighting coefficients are all periodic.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among other applications, ROM may be used as surrogates for prediction or as a replacement of costly solvers in optimisation routines. ROM have been proposed to represent horizontal axis turbine wakes, e.g., [9,10], but to the authors' knowledge, the present work is the first to propose a ROM for vertical axis turbines.…”
Section: Introductionmentioning
confidence: 96%
“…This theme issue of the Philosophical Transactions of the Royal Society A mainly builds on presentations [2][3][4][5][6][7][8][9][10][11] made at the EUROMECH Colloquium 576, Wind Farms in Complex Terrain, which took place at KTH Royal Institute of Technology in Stockholm, Sweden, over 3 days in June 2016. The main focus of the Colloquium was the various issues related to complex terrains, mainly from the aerodynamic, meteorological and noise-propagation points of view.…”
Section: Introductionmentioning
confidence: 99%